Thylakoid Membranes with Unique Photosystems Used to Simultaneously Produce Self‐Supplying Oxygen and Singlet Oxygen for Hypoxic Tumor Therapy. Issue 6 (14th January 2021) - Cheng, Yan; Zheng, Runxiao; Wu, Xiaqing; Xu, Keqiang; Song, Panpan; Wang, Yanjing; Yan, Jiao; Chen, Rui; Li, Xi; Zhang, Haiyuan
Abstract: Photodynamic therapy (PDT) efficacy has been dramatically limited by the insufficient oxygen (O2 ) level in hypoxic tumors. Although various PDT nanosystems have been designed to deliver or produce O2 in support of reactive oxygen species (ROS) formation, the feature of asynchronous O2 generation and ROS formation still results in the low PDT efficacy. Herein, thylakoid membranes (TM) of chloroplasts is decorated on upconversion nanoparticles (UCNPs) to form UCTM NPs, aiming at realizing spatiotemporally synchronous O2 self‐supply and ROS production. Upon 980 nm laser irradiation, UC NPs can emit the red light to activate both photosystem‐I and photosystem‐II of TM, the Z‐scheme electronic structure of which facilitates water to produce O2 and further to singlet oxygen ( 1 O2 ). UCTM NPs showed excellent biocompatibility, and can effectively remove the hypoxic tumor of mice upon 980 nm laser irradiation. This study develops a new PDT strategy for hypoxic tumor therapy based on photosynthesis. Abstract : Inspired by photosynthesis, thylakoid membranes with unique Z‐scheme electron transport property is extracted from chloroplasts and decorated on upconversion nanoparticles, which can simultaneously produce oxygen and singlet oxygen under near infrared laser irradiation. This design provides a new photodynamic therapy strategy to realize spatiotemporally synchronous oxygen self‐supply and reactive oxygen species production.